Rugby World Cup 2015: World Rugby injury surveillance study - Fuller, C. W.; Taylor, A.; Kemp, S. P. T.; Raftery, M. (British Journal of Sports Medicine, 2017)
Objective: To determine the incidence, severity and nature of injuries sustained during the Rugby World Cup (RWC) 2015 together with the inciting events leading to the injuries.